The association between pharmacy refill‐adherence metrics and healthcare utilisation: a prospective cohort study of older hypertensive adults. (10th April 2019) - Dillon, Paul; Smith, Susan M.; Gallagher, Paul; Cousins, Gráinne
Abstract: Aims: Methods that enable targeting and tailoring of adherence interventions may facilitate implementation in clinical settings. We aimed to determine whether community pharmacy refill‐adherence metrics are useful to identify patients at higher risk of healthcare utilisation due to low antihypertensive adherence, who may benefit from an adherence intervention. Methods: We conducted a prospective cohort study, recruiting participants ( n = 905) from 106 community pharmacies across the Republic of Ireland. Participants completed a structured interview at baseline and 12 months. Antihypertensive medication adherence was evaluated from linked pharmacy records using group‐based trajectory modelling (GBTM) and proportion of days covered (PDC). Healthcare utilisation included self‐reported number of hospital visits (emergency department visits and inpatient admissions) and general practitioner (GP) visits, over a 6‐month period. Separate regression models were used to estimate the association between adherence and number of hospital/GP visits. The relative statistical fit of each model using different adherence metrics was determined using the Bayesian information criterion (BIC). Results: For the number of hospital visits, significant associations were observed only for PDC but not for GBTM. Each 10% increase in refill‐adherence by PDC was significantly associated with a 16% lower rate of hospital visits (adjusted incidence rate ratio 0.84, 95% CI 0.72–0.98, P = 0.036). Poorer adherence using both measures was associated with higher GP visits. Improvements in BIC favoured models using PDC. Conclusions: Medication refill‐adherence, measured using PDC in community pharmacy settings, could be used to recognise poor antihypertensive adherence to enable effective targeting of clinical interventions to improve hypertension management and outcomes.